A review of menstrual sex education and management in women with congenital adrenal hyperplasia. Issue 5 (3rd September 2021) - Sanders, Caroline; Usipuik, Megan; Amyot, Emma; Koopmans, Erica; Hall, Joanne; Crawford, Leigh; Todd, Nicole; Jones, Tiffany
ABSTRACT: Congenital adrenal hyperplasia (CAH) encompasses a range of autosomal recessive inherited enzyme deficiencies that impact cortisol biosynthesis pathways. Although reported as a rare and lifelong disorder, it holds chronic health risks for individuals that can influence menstruation. The purpose of this environmental scan and integrative literature review was to identify health information pertinent to CAH and menstruation in order to inform health providers, increase patient education, and promote menstrual wellbeing. Analysis identified that while information about menses is reported, information about menstrual irregularities and their management in adolescents and women with CAH is uncertain. Furthermore, there is insufficient good quality research and knowledge on CAH and menstruation to inform health providers in their practice with this population. The need for individuals with CAH to access evidence-informed information is constrained by the state of current understanding and limitations in knowledge translation. The importance of having trustworthy and safe spaces in which to ask questions and draw on ethically sound, language appropriate, and evidence-informed material is paramount in supporting women's confidence and wellbeing across their lifetime. We encourage the building of stronger relationships between researchers, health providers, support groups and individuals to improve knowledge translation and dissemination regarding CAH and menstruation.